2022
DOI: 10.3390/agriculture12070899
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Feed Intake of Cattle Based on Jaw Movement Using a Triaxial Accelerometer

Abstract: The use of an accelerometer is considered as a promising method for the automatic measurement of the feeding behavior or feed intake of cattle, with great significance in facilitating daily management. To address further need for commercial use, an efficient classification algorithm at a low sample frequency is needed to reduce the amount of recorded data to increase the battery life of the monitoring device, and a high-precision model needs to be developed to predict feed intake on the basis of feeding behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Moreover, several papers recently appeared in the literature related to our works. Studies on feeding behaviors around calving in dairy cattle [22] and predicting the feed intake of cattle based on jaw movement using a triaxial accelerometer [23] are some of them. Although the approaches are different from ours, since feeding time estimation and feed intakes are related, further analysis would be worthwhile to investigate in more detail [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several papers recently appeared in the literature related to our works. Studies on feeding behaviors around calving in dairy cattle [22] and predicting the feed intake of cattle based on jaw movement using a triaxial accelerometer [23] are some of them. Although the approaches are different from ours, since feeding time estimation and feed intakes are related, further analysis would be worthwhile to investigate in more detail [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Cattle have historically been primarily evaluated on the basis of weight gain alone, as sensor technology to capture data at the individual level is a relatively recent development, and sensor uptake in the beef sector has lagged behind that of the dairy sector [ 26 , 27 , 28 ]. Models have previously been developed for cattle which predict DMI and residual feed intake [ 29 , 30 ], including models which utilise animal-mounted sensors [ 5 , 31 ]. Similar models have been developed for small ruminants [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ding et al ( 2022) evaluated an integrated machine-learning algorithm framework to identify jaw movements during feeding using a triaxial accelerometer at a relatively low sampling frequency, and it was also used to predict feed intake on the basis of the acceleration variables of ingesting and chewing activities. The results showed that three feeding activities-ingesting, chewing, and ingesting-chewing-could be effectively identified using the XGB and Viterbi algorithms with a precision of 99% [13].…”
Section: Precision Feed Intakementioning
confidence: 99%
“…Research has demonstrated the possibility of combining data from image, sound, and movement sensors with algorithms for dairy farm decision-making [10][11][12]. Ding et al (2022) used a wearable device equipped with accelerometers to measure the feeding behavior of cattle, and fourteen machine-learning models were established and compared in order to predict feed intake rates [13]. Gardenier et al (2018) presented a perception system that is suitable for automatic lameness detection.…”
Section: Introductionmentioning
confidence: 99%